1985
DOI: 10.1056/nejm198508223130802
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Metabolic Control with Insulin Pump Therapy

Abstract: To determine the long-term efficacy of insulin-pump therapy, we analyzed trends in glycosylated hemoglobin concentrations in 127 patients with Type I diabetes using insulin pumps for periods ranging from 13 to 47 months. In the first year of pump therapy the average glycosylated hemoglobin concentration improved in 83 per cent of the patients, as compared with the value before pump therapy. Although only 11 of the 127 subjects had normal glycosylated hemoglobin values before pump therapy, 33 had a normal avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
1
2

Year Published

1986
1986
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(31 citation statements)
references
References 7 publications
1
27
1
2
Order By: Relevance
“…Intensive management of diabetes is of great importance for improving longterm outcomes [1,2,36]. Using CSII regimes, it has been shown that rapid-acting human insulin analogs are effective in achieving and maintaining near-euglycemia [37,38]. In the present study, the patients responded to treatment with CSII with reductions in the levels of blood lipids, P-insulin, and required daily insulin doses, findings that support an improved insulin sensitivity [35].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Intensive management of diabetes is of great importance for improving longterm outcomes [1,2,36]. Using CSII regimes, it has been shown that rapid-acting human insulin analogs are effective in achieving and maintaining near-euglycemia [37,38]. In the present study, the patients responded to treatment with CSII with reductions in the levels of blood lipids, P-insulin, and required daily insulin doses, findings that support an improved insulin sensitivity [35].…”
Section: Discussionsupporting
confidence: 61%
“…Age was similar (P ¼ 0.82) in the two groups [improved HbA 1c 36 (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43) years; unchanged HbA 1c 36 (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41) years], as was diabetes duration, i.e. 20 (14-25) and 24 (15-28) years (P ¼ 0.85), respectively.…”
Section: Resultsmentioning
confidence: 92%
“…Mecklenburg et al 10 reported that 53% of adult patients discontinuing CSII therapy gave inflammation at the infusion site as their reason for quitting; infected infusion sites occurred in 29% of patients with a frequency of one infection every 27 patient-months, and there was a subgroup of patients who experienced repeated episodes of infection. 11 In the pediatric age group, Wood et al 12 reported that 21% of the children discontinuing CSII therapy cited infusion site issues as their reason for quitting.…”
Section: Figmentioning
confidence: 99%
“…Technical advancements in insulin pump fabrication and the use of rapid-acting insulin analogs in recent years have increased the safety and efficacy of CSII to successfully attain normoglycemia (2). It is estimated that Ͼ500,000 patients worldwide are currently using CSII (3).…”
mentioning
confidence: 99%